Seasonal Variability of the Cold Pool Over the Mid‐Atlantic Bight Continental Shelf. Issue 11 (13th November 2018) - Chen, Zhuomin; Curchitser, Enrique; Chant, Robert; Kang, Dujuan
Abstract: The Mid‐Atlantic Bight (MAB) Cold Pool is a distinctive cold (lower than 10 °C) and relatively fresh (lower than 34 practical salinity unit) water mass. It is located over the middle and outer shelf of the MAB, below the seasonal thermocline, and is attached to the bottom. Following this definition, we put forward a method that includes three criteria to capture and quantify Cold Pool characteristics, based on a 50‐year (1958–2007) high‐resolution regional ocean model hindcast. The seasonal climatology of the Cold Pool and its properties are investigated during its onset‐peak‐decline cycle. Three stages of the Cold Pool event are defined according to its evolution and characteristics. The Cold Pool cores travel along the 60‐m isobath starting south of the New England shelf to the Hudson Shelf Valley at a speed of 2–3 cm/s. Furthermore, the northern extent of the Cold Pool retreats about 2.6 times faster than the southern extent during the summer progression. The heat balance of near‐bottom waters over the MAB and Georges Bank is computed and it is found that the heat advection, rather than vertical diffusion, dominates the resulting spatial patterns of warming. Possible origins of the Cold Pool are investigated by performing a lead‐lag correlation analysis. Results suggest that the Cold Pool originates not only from local remnants of winter water near the Nantucket Shoals, but has an upstream source traveling in the spring time from the southwestern flank of the Georges Bank along the 80‐m isobath. Plain Language Summary: The Mid‐Atlantic Bight (MAB) Cold Pool is a bottom‐trapped relatively cold and fresh water mass over the middle and outer continental shelf. It is a seasonal thermal feature that emerges during spring and summer when the water column is warmer at the surface. We use three criteria to quantify the Cold Pool and investigate its seasonal evolution of properties. We find the Cold Pool typically experiences an onset‐peak‐decline cycle during a year. Its coldest part travels along the 60‐m isobath at a speed of 2–3 cm/s from the south of the Nantucket Shoals to the Hudson Shelf Valley. During its seasonal collapse, the northern and southern boundaries retreat at different speeds, with the northern boundary retreating 2.6 times faster. In order to investigate relative importance of vertical mixing and advection of heat, we build a heat balance of the water column below 30 m depth. Results suggest that vertical mixing is the main reason for the warming in the Cold Pool, however, horizontal and vertical advection of heat that regulates the spatial difference in warming rates of the Cold Pool. We further discuss the possible origins of the Cold Pool. Key Points: The Cold Pool travels equatorward along the 60‐m isobath at a speed of 2–3 cm/s with a warming rate of about one degree Celsius per month The northern extent of the Cold Pool retreats 2.6 times faster than the southern extent Vertical and horizontal advection, rather than vertical diffusion, modulate the geographical differences in warming trends